Becoming Julia de Burgos : the making of a Puerto Rican icon - Pérez Rosario, Vanessa (University of Illinois Press, 2014)
While it is rare for a poet to become a cultural icon, Julia de Burgos has evoked feelings of bonding and identification in Puerto Ricans and Latinos in the United States for over half a century. In this book, the author examines Julia de Burgos' development as a writer, her experience of migration, and her legacy in New York City.